Retrospective study on the outcomes of Fassier-Duval nailing and osteotomy for the treatment of long bone fractures or deformities in the lower extremities in children with osteogenesis imperfecta - Jin, Bin; Chen, Yuan; Bai, ChuanQing; Ma, HaiLong; Zhu, JunChen (Frontiers in Surgery, 2025)
BackgroundOsteogenesis imperfecta (OI) is a rare hereditary disorder characterized by bone fragility and deformity, frequently requiring surgical intervention to restore limb alignment and stability. Traditional intramedullary fixation devices are limited in growing children. The Fassier-Duval (FD) nail, designed to elongate with growth, offers potential advantages when combined with corrective osteotomy. This study retrospectively evaluated the clinical outcomes of FD nail fixation with osteotomy for long bone fractures and deformities in children with OI.MethodsWe retrospectively reviewed 33 pediatric OI patients (23 males, 10 females) who underwent FD nail implantation for 63 long bones of the lower extremities (42 femurs, 21 tibias) between December 2016 and September 2023. According to Sillence classification, 5 patients were type I, 18 type III, and 10 type IV. Thirty-two bones presented with acute fractures, 9 with isolated deformities, and 22 with fracture plus deformity. Radiographic outcomes, number of osteotomies, complication rates, revision surgeries, and functional results (PODCI and BAMF scores) were analyzed.ResultsThe mean age at initial surgery was 7 years, with a median follow-up of 55 months. The average time to bone union was 5.3 weeks (range, 4–7). For patients with deformities, mean preoperative coronal and sagittal angulations were 31.9° and 34.5°, corrected postoperatively to 0.9°and 1.1°, respectively. Thirteen revision surgeries were required, with an overall revision rate of 20.63%. Complications included refracture (n = 4) and nail failure (n = 9); no nonunion, nerve injury, or infection occurred. PODCI scores improved from 40.4 to 45.5, and BAMF scores from 3.1 to 6.1 (both P < 0.0001).ConclusionsFD nail fixation combined with osteotomy is effective for treating long bone fractures and deformities in children with OI. It provides reliable deformity correction, promotes rapid bone healing, and significantly improves motor function and quality of life, with acceptable complication and revision rates.